Antarctic haze phenomena at Syowa Station, Antarctica: seasonal features and impacts on atmospheric chemistry - Keiichiro Hara; Kano Osato; Masanori Yabuki; Kazuo Osada; Naohiko Hirasawa; Masataka Shiobara; Takashi Yamanouchi (npj Climate and Atmospheric Science)
Abstract Despite the cleanest conditions, haze phenomena were observed at Syowa Station, Antarctica. During our measurements period of 1997–2022, 113 haze events were identified. General characteristics of Antarctic haze such as duration and horizontal scale were obtained from haze event analyses. Antarctic haze near the surface was identified mostly during May–October. Seasonal features of the Antarctic haze appearance were that they were maximal in August and were associated with strong wind conditions and sea-ice extent. Aerosol enhanced layers (AELs) appeared in the surface – free troposphere (ca. 4 km). AELs were identified also in mid-April – October. Furthermore, surface ozone (O3) was depleted during the Antarctic haze. The O3 depletion amount was maximal during August and minimal during polar night (June). Findings suggest that Antarctic haze phenomena make important contributions to atmospheric oxidative capacity and cloud processes in the Antarctic troposphere.